2020
DOI: 10.5713/ajas.19.0026
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide scans for detecting the selection signature of the Jeju-island native pig in Korea

Abstract: Objective: The Jeju native pig (JNP) found on the Jeju Island of Korea is a unique black pig known for high-quality meat. To investigate the genetic uniqueness of JNP, we analyzed the selection signature of the JNP in comparison to commercial pigs such as Berkshire and Yorkshire pigs.Methods: We surveyed the genetic diversity to identify the genetic stability of the JNP, using the linkage disequilibrium method. A selective sweep of the JNP was performed to identify the selection signatures. To do so, the popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The Korean peninsula is one of the largest pig consuming country with its Jeju native black pig (JNP) is an indigenous variety of Korean pig with high-quality meat content, redness and nutrition value 4 , 5 . Superior taste leads to an increase in JNP demand with every passing day but less productivity and fertility made it difficult to sustain the demand 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The Korean peninsula is one of the largest pig consuming country with its Jeju native black pig (JNP) is an indigenous variety of Korean pig with high-quality meat content, redness and nutrition value 4 , 5 . Superior taste leads to an increase in JNP demand with every passing day but less productivity and fertility made it difficult to sustain the demand 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In JNP, the notable genes containing nsSNPs were Transforming growth factor beta 2 proprotein (TGFB2), glutathione S-transferase kappa 1 (GSTK1) and ATP-binding cassette subfamily A member 8 (ABCA8). In previous study, TGFB2 gene were reported to be related to the developmental growth in JNP in comparison to the Berkshire pigs (Lee, Shin, et al 2020 ). Members of the glutathione S-transferase (GST) family constitute a large class of cytoplasmic, membrane-bound, multigene, and multifunctional enzymes (Hayes et al 2005 ).…”
Section: Discussionmentioning
confidence: 90%
“…π ratio analysis is also a common detection method used to focus on the polymorphisms of a specific population based on gene heterozygosity, and a larger π ratio indicates a higher polymorphism [ 27 ]. These methods have been widely used in the selection signal detection of livestock [ 28 , 29 ]. In Zhang’s study, F ST and π ratio analyses were combined; used to define the genomic selection region of the Wannan black pig; and found selected genes associated with growth, immunity, and digestive functions [ 30 ].…”
Section: Discussionmentioning
confidence: 99%